Redução de vogais altas pretônicas no português de Belo Horizonte: uma abordagem baseada na gradiência - Ricardo Fernandes Napoleao de Souza (2012)
This thesis investigated the reduction of high vowels [i] and [u] in prestressed CVC syllables closed by the sibilant [s] in the Belo Horizonte dialect of Brazilian Portuguese. We aim to demonstrate that the reduction of segments is a gradient phenomenon which may or may not consolidate itself as thourough vowel deletion. The data were analyzed based on the dynamic phonological theories of Usage-based Phonology (BYBEE, 2001; 2010), Exemplar Models (PIERREHUMBERT, 2001; 2003) and Articulatory Phonology (BROWMAN & GOLDSTEIN, 1986; 1992). Sixteen native speakers (8 male, 8 female) of two different age groups (21-25 and 35-62 year old) produced 1920 tokens of 60 words in carrier-sentences at two different speech rates presented in a controlled experiment. The results obtained were examined in two ways: a binary analysis and a gradient analysis. The data gathered were analyzed statistically and results demonstrate the relevance of vowel type, speech rate and stress in the occurrence of high vowel reduction. The data show that age is an important factor in high vowel reduction as observed. The results of the gradient analysis support the claims of Usage-based Phonology and Exemplar Models regarding gradience in language change phenomena. Half the data was examined with the help of an electroglottograph as a means of evaluating variation in prestressed vowel production on an articulatory basis. Results indicate that the vowel reduction phenomenon in question can be understood as an overlap of glottal and vowel gestures, according to the claims of Articulatory Phonology theory. Acoustic and articulatory analyses provide evidence of the relationship between phonetic and phonological levels by showing that phonetically-motivated changes pave the way for phonological change.